An amebic liver abscess in a female child with successful recovery in a non-endemic area: a case report - Jia, Jihang; Guo, Qin (Frontiers in Pediatrics, 2025)
We report the case of a 2-year-and-11-month-old female child who presented with a 10-day history of recurrent fever and abdominal pain, accompanied by significantly elevated inflammatory markers. Initially, incomplete Kawasaki disease (IKD) was strongly suspected; however, the patient continued to experience recurrent high fever and abdominal pain despite treatment with intravenous immunoglobulin (IVIG) and antibiotics. Enhanced thoraco-abdominal computed tomography (CT) imaging revealed hepatomegaly and the presence of an abscess in the anterosuperior segment of the right lobe of the liver. The patient subsequently underwent a surgical intervention due to the progression of her symptoms, including worsening fever, abdominal pain, and the development of new-onset shortness of breath. The postoperative immunohistochemical analysis identified Entamoeba histolytica (E. histolytica) trophozoites, confirming the diagnosis of an amebic liver abscess (ALA). Following the diagnosis, the patient was treated with 10 days of oral metronidazole. A follow-up CT scan conducted 4 months later showed complete resolution of the liver abscess and normalization of liver function. While amebiasis is rare in pediatric populations, it should be considered in the differential diagnosis of liver abscesses, even in non-endemic regions.